New Regional headquarters for Government Institutions Pension Fund (GIPF) and office park in Katima Mulilo: shift/transformation of identity through spatial evolution - Mwazi, Vernon M. (University of the Free State, 2015)
This dissertation aims at investigating the existing townscape and repairing the hidden bonds that have been severed. The use of architecture sensitively will reignite a series of chain reactions that ultimately result in spatial arrangements that define space and result in the positive identification of place. Through the analysis of the macro, meso, micro and historical contexts of the Zambezi region as well as Katima Mulilo, specific contextual catalysts were identified and used to understand as well as to decipher the everyday dialogue between: -Rural vs Urban -Nature vs Built environment, -Built environment vs Man and -Contemporary vs Traditional. The coded message was then revealed and embedded into the architectural language as part of the solution to the question. Most small towns across Namibia are still in their infancy with regard to urbanisation and rely on the rural user for their growth and development and are being designed using models that are not suitable for their contexts. As a result, the bonds that link these clusters of communities are eradicated and buried by more global, economic links that alienate and create divisions among the community. Government institutional buildings are the epitome of social centres aimed at the unification of different communities regardless of creed or colour and thus will be the building typology under investigation in this dissertation.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2015
Keywords: Built environment; Architecture-Urban nature; Namibia-Architecture-Towns